Outcome of Extracorporeal Membrane Oxygenation for Pediatric Patients With Neoplasm: An Extracorporeal Life Support Organization Database Study (2000–2019). Issue 5 (28th February 2022) - Suzuki, Yota; Cass, Samuel H.; Kugelmann, Andrew; Mobli, Keyan; Taylor, Williams P.; Radhakrishnan, Ravi S.
Abstract : OBJECTIVES: This study update in usage and outcomes of pediatric extracorporeal membrane oxygenation (ECMO) for patients with neoplasm analyzed according to demographics, clinical variables, and complications. DESIGN: Retrospective database review of the Extracorporeal Life Support Organization registry from the last 2 decades (2000–2019). The data were divided between two decades in order to compare patients' backgrounds and outcomes over time. SETTING: ECMO centers reporting to Extracorporeal Life Support Organization. PATIENTS: Patients equal to or younger than 18 years old with International Classification of Diseases, 9th Revision and International Classification of Diseases, 10th Revision codes that referred to neoplasms who were managed with ECMO. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Demographics, cancer subtype, clinical variables, and ECMO complications were assessed in relation to the primary study outcome of survival to hospital discharge. Nine-hundred two patients met inclusion criteria; 699 patients were in the latest decade, which is more than three times the number from the previous decade (203 patients). On univariate analysis, compared with the previous decade, in the later decade, ECMO was more frequently applied in patients with pre-ECMO cardiac arrest (31.3% vs 17.1%; p < 0.001), and/or lower oxygenation index (38.0 vs 48.1; p < 0.001). We failed to identify a difference in survival between the 2 decades (42.8% vs 37.9%; p = 0.218). On multivariable analysis, diagnosis of hematologic malignancy, post-cardiopulmonary resuscitation support type, hematopoietic stem cell transplant, and age older than seven were each associated with greater odds of mortality. CONCLUSIONS: The use of ECMO in children with neoplasm has expanded over the latest decade with changes in patient selection. Mortality remains unchanged. Hence, although the clinician still should stay cautious in its application, ECMO can be considered as an option to rescue pediatric oncologic patients in the setting of worsening cardiopulmonary status in the PICU.